Maya and the rising dark - Barron, Rena (Houghton Mifflin Harcourt, 2020)
Twelve-year-old Maya is the only one in her neighborhood who sees strange things like werehyenas stalking the streets and a man made of shadows who plagues her dreams. When her father goes missing, Maya learns that he is the guardian of the veil between our world and the Dark, where the Lord of Shadows has an army waiting. Maya also discovers that she's half orisha and half human and that her neighborhood is considered a safe haven. But the veil is failing and the Lord of Shadows is determined to destroy the human world. It's up to Maya to stop him and save her father.